The Patient Controlled Analgesia method [Hasta Kontrollü Analjezi yöntemi] - (:unkn) unknown (My University, 2003)
The Patient Controlled Analgesia (PCA) method, which enables the patient to define the analgesic delivery time and consumption, though eliminating the personnal differences, seems to be an ideal analgesic treatment method. The results of the studies comparing the analgesic consumption, efficacy and side effects of PCA and conventional intermittent parenteral drug administration, are controversial. But if the patient, analgesic drug and delivery regimen are selected properly, PCA is an effective and safe method, especially in clinics with insufficient number of healthcare professionals.
Keywords: Efficacy; Patient controlled analgesia; Side effects